1970
DOI: 10.1037/h0029637
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of therapist and client social class.

Abstract: A number of studies suggest that therapist-client similarity is an important factor in client continuation in therapy and outcome (Carson & Heine, 1962;Heine & Trosman, 1960;Overall & Aaronson, 1963).Of particular interest is the series of studies by Carson (1967), McNair, Callahan, and Lorr (1962), and Whitehorn and Betz (1960 which tend to indicate that positive client outcome is related to therapist-client social class similarity. The existence of this relationship has been implied but not tested directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1975
1975
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…
This study replicates Mitchell and Namenek's (1970) study in which therapists' estimates of their typical clients' social class were significantly related to the therapist's own discipline and self-ascribed socioeconomic background. The relationship between the therapist's discipline and socioeconomic background was also significant.
…”
supporting
confidence: 75%
See 3 more Smart Citations
“…
This study replicates Mitchell and Namenek's (1970) study in which therapists' estimates of their typical clients' social class were significantly related to the therapist's own discipline and self-ascribed socioeconomic background. The relationship between the therapist's discipline and socioeconomic background was also significant.
…”
supporting
confidence: 75%
“…Since the present findings were not consistent with those of Mitchell and Namenek (1970), we decided to compare the therapists' social-class distribution, which was based on self-report (Study 1), with the distribution, which was based on an independent determination (Study 2). We found that the two distributions were not significantly different for all therapists, x z (2l) = 2.00, for the clinical psychologists, x 2 (2) = .857, or for the psychiatrists, X 2 (2) = 1.12.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…An interesting study by Mitchell and Namenek (1970) When therapists in private practice were considered, there was no difference in SES background between psychologists and psychiatrists and yet psychiatrists saw more upper class patients and psychologists more lower class patients.…”
Section: Scalementioning
confidence: 99%